G416(P) A hospital-based survey of oral health knowledge and practices of parents and carers in derbyshire. (12th March 2018) - Ong, Q; Utting, C; Whiston, S; Braithwaite, M; Sanders, H; Okike, I; Dickenson, A
Abstract : Background: Tooth decay is largely a preventable disease. It affects almost a quarter of 5-year-olds and was the most common reason for hospital admission for children aged 5–9 years in 2014–2015 in England. There is a huge financial burden of tooth decay on the NHS. The aim of our survey was to ascertain the oral health knowledge and practices of parents and carers of children attending the Derbyshire Children's Hospital. Method: Parents or carers of children attending our hospital were surveyed between August and October 2017 using an anonymised paper-based questionnaire. It was developed using the 'Delivering Better Oral Health' document, which is an evidence-based toolkit published by Public Health England. The questions assessed knowledge, oral hygiene regime and dietary habits. Oral health information leaflet was provided after completion of the questionnaire. Results: Derbyshire Children's hospital is a busy District General hospital with ~87 000 visits in 2016. A total of 800 surveys were completed representing about 1% of our expected attendance per year. Most, 414 (52%) were ≥7 years old, whilst 217 (27%) were 0–3 years and 166 (21%) were 4–6 years old. Only 187/800 (23%) of children were reported to be brushing their teeth correctly. Additionally, 114/383 (30%) of children≤6 years of age do not regularly receive appropriate help with brushing. This was significantly worse amongst 4–6 year olds, p=0.006. Although 711 (89%) of parents/carers were aware of free NHS dental care for children, only 246 (31%) visited or planned to visit a dentist at the earliest opportunity i.e. as soon as teeth erupt. Parents/carers reported that 172 (22%) of children had unhealthy snacking habits. Conclusion: To our knowledge, this is the first hospital based survey in England. There appears to be gaps in the knowledge of parents/carers regarding good oral health. Our survey also highlighted unhealthy dietary habits with potential implications on oral health and wider impact on health. Oral health should remain in everyone's agenda to enable every child grow up free from tooth decay and have the best start in life. We propose oral health promotion and education for parents, carers and children. Hospital visits provide an excellent opportunity.